Analisis Penambahan Kapasitas Udara Bertekanan untuk Pneumatik pada Mesin Kertas 01 di Perusahaan Kertas, Bekasi - Jazid Rizkon; Anastasia Lidya Maukar; Ineu Widaningsig Sosodoro (President University, 2018)
In paper mills, paper presses, paper rolling, and automatic valves are very important machines for the continuity of the production process. But at present, problems often occur, namely the machines cannot work optimally, because the need for compressed air for pneumatic tools is not enough fulfilled. To ensure this, the capacity calculation of the pressurized air compressor and the need for pressurized pneumatic tools are carried out. The results of the calculation show that the pressurized air requirements of pneumatic tools are greater than those produced by the kompresor with a difference of 2,972 litres/minute. To get the best decision, an Equivalent Uniform Annual Cost (EUAC) analysis is performed to determine the economic life of the compressor machines currently in use. In addition, an inspection of compressor damage data was also carried out. The results of the analysis show that the replacement of the compressor does not need to be done because the current engine life is under the economic age. Thus, the decision taken is to purchase a new compressor with a capacity of 28,000 litres/minute. The calculation using the present worth cost (PWC) analysis obtained the smallest total cost with consideration of the additional energy costs is Atlas Copco GA160 Compressor worth Rp 55,094,911,134. Without considering additional energy costs, the results of the calculation of the smallest total PWC is the choice of Kaeser DSD250 amounting to Rp. 8,044,785,017. Then after sensitivity analysis with consideration of interest rates and electricity costs, Atlas Copco GA160 has the lowest total cost. Thus, the changes in interest rates and an increase of electricity costs are not sensitive enough to the selection of machines for investment.